MECHANISM OF EXAMINATION AND PROOF IN THE SETTLEMENT OF BUSINESS COMPETITION DISPUTES BY THE BUSINESS COMPETITION SUPERVISORY COMMISSION (STUDY OF DECISION No.04/ICC- I/2016) - Ratih Ayunda; Bisdan Sigalingging (Inspiring Law Journal, 2026)
Healthy business competition is an important element in realizing a fair and efficient economy. However, in practice, there are still violations of business competition laws, especially the practice of pricing that has the potential to cause unfair business competition. To enforce these provisions, Law Number 5 of 1999 establishes the Business Competition Supervisory Commission (ICC) as an independent institution that is authorized to conduct examinations and proofs of business actors who are suspected of violating the provisions of the competition law. This study aims to analyze the mechanism of examination and proof by ICC in resolving business competition disputes through a study of Decision Number 04/ICC-I/2016. The research method used is normative legal research with a legislative approach and a case approach.  The results of the study show that the examination and proof mechanism carried out by ICC has been carried out in accordance with the provisions of the applicable laws and regulations. In the process, ICC uses evidence in the form of witness statements, expert statements, letters and documents, instructions, and statements from business actors, including the application of indirect evidence in pricing cases. Decision No. 04/ICC-I/2016 shows that the use of indirect evidence can strengthen the confidence of the commission panel in proving the existence of violations, although in practice there is still debate regarding evidentiary standards and legal certainty for business actors.